2019
DOI: 10.1007/s00220-019-03642-x
|View full text |Cite
|
Sign up to set email alerts
|

Dirac Operators on Hypersurfaces as Large Mass Limits

Abstract: We show that the eigenvalues of the intrinsic Dirac operator on the boundary of a Euclidean domain can be obtained as the limits of eigenvalues of Euclidean Dirac operators, either in the domain with a MIT-bag type boundary condition or in the whole space, with a suitably chosen zero order mass term.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…In contrast to the 2D setting, A ϑ was not directly investigated for general boundary parameters in 3D, as far as we know only the particular MIT bag operator is well studied. We emphasize the recent papers [2,56] for the analysis of general properties of the MIT bag operator and [3,9,24,54,62], where it is shown that the MIT bag boundary conditions and their 2D analogues can be interpreted as infinite mass boundary conditions (i.e., Ω is surrounded by a medium with infinite mass). The strategy developed in [56] employing Calderón projections can also be used to study the self-adjointness of Dirac operators of the form (1.1).…”
Section: Introductionmentioning
confidence: 96%
“…In contrast to the 2D setting, A ϑ was not directly investigated for general boundary parameters in 3D, as far as we know only the particular MIT bag operator is well studied. We emphasize the recent papers [2,56] for the analysis of general properties of the MIT bag operator and [3,9,24,54,62], where it is shown that the MIT bag boundary conditions and their 2D analogues can be interpreted as infinite mass boundary conditions (i.e., Ω is surrounded by a medium with infinite mass). The strategy developed in [56] employing Calderón projections can also be used to study the self-adjointness of Dirac operators of the form (1.1).…”
Section: Introductionmentioning
confidence: 96%
“…Eventually, in [27], a detailed study of the spectral properties of A 0,τ for purely scalar potentials was provided; in particular, it was shown that the discrete eigenvalues in the large mass limit are characterized by an effective operator on the surface . Furthermore, there is a great interest recently in the study of self-adjoint Dirac operators on domains with boundary conditions, see, e.g., [2,3,10,11,25,30,31,35,38].…”
mentioning
confidence: 99%
“…Various mathematical studies have been undertaken, starting with a rigorous mathematical derivation of such Hamiltonians, see e.g. [19] for the effective Hamiltonian derivation or [3,8,30,38] for the justification of the so-called infinite mass boundary conditions. Many properties of such operators have been investigated as their self-adjointness in bounded domains with specified boundary conditions or coupled with the so-called δ-interactions, see [9,11].…”
Section: Introductionmentioning
confidence: 99%